Pengaruh Kepemimpinan Manajemen Rumah Sakit Dalam Iklim Keselamatan Pasien di Rumah Sakit Sentra Medika Cibinong Tahun 2013 - Suwignjo, Regina Angelia (UI Scholars Hub, 2015)
Transformational leadership as one of leadership style become the most important factor to build a patient safety culture in hospital environment and ensure the program will run succesfully to promote patient safety hospital services. The transformational leadership style indicator is intellectual stimulation, inspirational motivation, idealized influence, and individual consideration. Indicator of patient safety climate is management commitment, employee empowerment, reporting system, reward system and organizational identity. The aim of the study was to obtain every leadership factor that affect patient safety climate and which one is the most prominent leadership factor that influenced the patient safety climate in Sentra Medika Cibinong Hospital. This quantitative study was design with cross section design, the measurement tools for this study was questionnaires and observation. The result showed a significant correlation between the leadership factors such as inspirational motivation and idealization influence build the patient safety climate in Sentra Medika Cibinong Hospital. The prominent leadership factor that shown in this study is idealization influence. Conclusion of this study is idealization influence and inspirational motivation to empower the employee through training and instill organization identity from top management would be beneficial factor.